Caracterización de los residuos sólidos que se generan en Provefarma S.A. en el sector del Cortijo del cantón Rumiñahui, provincia de pichincha, 2014 - Mena Álvarez, Luis Alberto (2014)
The investigation is about the classification of solid residues in “Proverfarma S.A” present in the different areas of distribution of Los Shyris Ave km 5 ½, on the way to Sangolqui. This job was executed through conversations with the department of SSOA, hygiene and cleaning personnel, people of the medical department, and collaborators of each area. Additionally, the opinions of experts related to the field of study were also obtained. To classify and describe the solid residues in Provefarma s.a the Mexican norms NMX-AA-1985 were adapted; there is norm NMX-AA-015 that is used for the quartering method, and the NMX-AA-019 establishes a method to determine the volumetric weight of solid residues in the place where the quartering method takes place, the Mexican norm NMX-AA-022 establishes the selection and quantification method of the by-products that the solid residues contain....